2014
DOI: 10.1002/met.1475
|View full text |Cite
|
Sign up to set email alerts
|

The observed and modelled influence of the Madden-Julian Oscillation on East African rainfall

Abstract: ABSTRACT:The aim of this work is to determine to what extent precipitation modulated by the Madden-Julian Oscillation (MJO) over East Africa can be forecast by the operational global Met Office Unified Model (MetUM). Observed patterns of rainfall were analysed over Kenya, Tanzania and Uganda and used to validate MetUM forecasts made over the period [2005][2006][2007][2008][2009][2010][2011][2012]. It was found that there is a large seasonal dependence on the MJO for episodes of enhancement and suppression of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 26 publications
7
26
0
Order By: Relevance
“…Compared to the average days in each phase (Figure e, grey dots), this number is particularly high. During these phases East Africa is known to experience enhanced rainfall conditions over the highlands (Pohl and Camberlin, ; Hogan et al ., ). Furthermore, analysis by Hogan et al .…”
Section: Case‐study Of 2018 Long Rainssupporting
confidence: 91%
See 1 more Smart Citation
“…Compared to the average days in each phase (Figure e, grey dots), this number is particularly high. During these phases East Africa is known to experience enhanced rainfall conditions over the highlands (Pohl and Camberlin, ; Hogan et al ., ). Furthermore, analysis by Hogan et al .…”
Section: Case‐study Of 2018 Long Rainssupporting
confidence: 91%
“…Furthermore, analysis by Hogan et al . () gives an indication that phase 3 tends to be accompanied by anomalous low‐level westerlies across East Africa, consistent with the Congo influence presented here. In addition, our work shows there were more days in the 2018 long rains, than in an average year, with an active MJO, i.e., there were more days with amplitude greater than 1.…”
Section: Case‐study Of 2018 Long Rainssupporting
confidence: 91%
“…Wet conditions tend to occur in the first half of the MJO cycle along the coast and in the second half of the MJO cycle in the highlands [ Hogan et al ., ]. The contrasting rainfall conditions found in the two regions for the opposite MJO phases are strongly correlated with the pressure gradient between the Indian and Atlantic Oceans [ Pohl and Camberlin , ].…”
Section: Intraseasonal Variabilitymentioning
confidence: 99%
“…They are therefore not directly comparable to the MJO composites by Pohl and Camberlin () or Hogan et al . (). In years with average MJO activity (positive and negative ω anomalies of average amplitude crossing East Africa) the magnitude of wet anomalies is smaller than during strong MJO years.…”
Section: Mechanisms Of Teleconnectionsmentioning
confidence: 99%
“…dynamical constraints on cloud top outflow and upper‐level shear: Collimore et al, ) would be challenging for models that use parametrized convection. The MJO has been linked to intraseasonal spells of enhanced or suppressed rainfall in East Africa, depending on MJO phase (Pohl and Camberlin, ; Hogan et al, ). These studies have found that intraseasonal spells tend to have an east–west spatial structure in which rainfall anomalies over coastal and highland regions are out of phase.…”
Section: Introductionmentioning
confidence: 99%